UDP-Sugar Producing Pyrophosphorylases: Distinct and Essential Enzymes With Overlapping Substrate Specificities, Providing de novo Precursors for Glycosylation Reactions - Decker, Daniel; Kleczkowski, Leszek A. (Frontiers in Plant Science, 2019)
Nucleotide-sugars are the key precursors for all glycosylation reactions, and are required both for oligo- and polysaccharides synthesis as well as protein and lipid glycosylations. Among all nucleotide-sugars, UDP-sugars are the most important precursors for biomass production in nature (e.g. synthesis of cellulose, hemicellulose and pectins for cell wall production). Several recent studies have already suggested a potential role for UDP-Glc in plant growth and development, and UDP-Glc has also been suggested as a signaling molecule, in addition to its precursor function. In this review, we will cover primary mechanisms of formation of UDP-sugars, by focusing on UDP-sugar metabolizing pyrophosphorylases. The pyrophosphorylases can be divided into three families: UDP-Glc pyrophosphorylase (UGPase), UDP-sugar pyrophosphorylase (USPase) and UDP-N-acetyl glucosamine pyrophosphorylase (UAGPase), which can be distinguished both by their amino acid sequences and by differences in substrate specificity. Substrate specificities of these enzymes are discussed, along with structure-function relationships, based on their crystal structures and homology modeling. Earlier studies with transgenic plants have revealed that each of the pyrophosphorylases is essential for plant survival, and their loss or a decrease in activity result in reproductive impairment. This constitutes a problem when studying exact in vivo roles of the enzymes using classical reverse genetics approaches. Thus, strategies involving the use of specific inhibitors (reverse chemical genetics) are also discussed. Further characterization of the properties/roles of pyrophosphorylases should address fundamental questions dealing with mechanisms and control of carbohydrate synthesis and may allow to identify targets for manipulation of biomass production in plants.